Is the Interplay between Epigenetic Markers Related to the Acclimation of Cork Oak Plants to High Temperatures? - Correia, Barbara; Valledor, Luis; Meijón, Mónica; Rodriguez, José Luis; Dias, Maria Celeste; Santos, Conceição; Cañal, Maria Jesus; Rodriguez, Roberto; Pinto, Glória (PLoS ONE, 2013)
Trees necessarily experience changes in temperature, requiring efficient short-term strategies that become crucial in environmental change adaptability. DNA methylation and histone posttranslational modifications have been shown to play a key role in both epigenetic control and plant functional status under stress by controlling the functional state of chromatin and gene expression. Cork oak (Quercus suber L.) is a key stone of the Mediterranean region, growing at temperatures of 45°C. This species was subjected to a cumulative temperature increase from 25°C to 55°C under laboratory conditions in order to test the hypothesis that epigenetic code is related to heat stress tolerance. Electrolyte leakage increased after 35°C, but all plants survived to 55°C. DNA methylation and acetylated histone H3 (AcH3) levels were monitored by HPCE (high performance capillary electrophoresis), MS-RAPD (methylation-sensitive random-amplified polymorphic DNA) and Protein Gel Blot analysis and the spatial distribution of the modifications was assessed using a confocal microscope. DNA methylation analysed by HPCE revealed an increase at 55°C, while MS-RAPD results pointed to dynamic methylation-demethylation patterns over stress. Protein Gel Blot showed the abundance index of AcH3 decreasing from 25°C to 45°C. The immunohistochemical detection of 5-mC (5-methyl-2′-deoxycytidine) and AcH3 came upon the previous results. These results indicate that epigenetic mechanisms such as DNA methylation and histone H3 acetylation have opposite and particular dynamics that can be crucial for the stepwise establishment of this species into such high stress (55°C), allowing its acclimation and survival. This is the first report that assesses epigenetic regulation in order to investigate heat tolerance in forest trees.
The following values have no corresponding Zotero field: publisher: Public Library of Science accession-num: 23326451
Keywords: Acclimatization; Acclimatization: genetics; Acetylation; Blotting; CHROMATIN; CORK oak (citation; Deoxycytidine; Deoxycytidine: analogs & derivatives; Deoxycytidine: metabolism; DNA; DNA methylation; Electrolytes; Electrolytes: metabolism; Epigenesis; Gene expression; Genetic; Genetic Markers; Genome; Heat-Shock Response; Heat-Shock Response: genetics; Histones; Histones: metabolism; Physiological; Physiological: genetics; Plant; Plant Leaves; Plant Leaves: metabolism; Plant: genetics; POST-translational modification; Quercus; Quercus: genetics; Quercus: physiology; Random Amplified Polymorphic DNA Technique; Stress; tags); Temperature; TREES -- Research; Western

Frequent cytoplasmic exchanges between oak species that are not closely related: Quercus suber and Q. ilex in Morocco - Belahbib, N; Pemonge, M.-H. H; Ouassou, A; Sbay, H; Kremer, A; Petit, R J (Molecular Ecology, 2001)
Chloroplast (cp) and mitochondrial (mt) DNA variation were studied in 97 populations of cork oak (Quercus suber) in Morocco; in 31 of these populations, holm oak (Quercus ilex), a clearly distinct species, also occurred and was compared with Q. suber. Three cpDNA and one mtDNA primer pairs were used in the survey, each in combination with one restriction enzyme. Six haplotypes belonging to two very divergent lineages were detected; one lineage predominates in each species, and is probably ancestral, as inferred from comparisons with other oak species. In the mixed-species populations, cytoplasmic genomes were frequently shared across species, as indicated by an introgression ratio of 0.63. This index is a new measure of the propensity of species to share locally genetic markers, varying from zero (complete differentiation) to one (no differentiation). By contrast, more closely related deciduous oak species (Q. robur, Q. petraea and Q. pubescens) have introgression ratios varying from 0.82 to 0.97. The introgression events appear to have been more frequent in the direction Q. ilex (female) × Q. suber (male), a finding which seems attributable to the flowering phenology of these two species. This asymmetry may have favoured immigration of Q. suber beyond its main range, in regions already colonized by Q. ilex. There, rare hybridization and further introgression through long distance pollen flow have established populations that are morphologically indistinguishable from Q. suber but that have cytoplasmic genomes originating from the local Q. ilex populations.
Keywords: Chloroplast; Chloroplast: genetics; cpDNA; DNA; Evolution; Genetic; Genetic Markers; Genetic Variation; Genetic: genetics; geographical structure; Haplotypes; Hybridization; introgression; Mitochondrial; Mitochondrial: genetics; Models; Molecular; Morocco; mtDNA; PCR–RFLP; Quercus; Quercus: genetics; Trees; Trees: genetics

Frequent cytoplasmic exchanges between oak species that are not closely related: Quercus suber and Q. ilex in Morocco - Belahbib, N.; Pemonge, M.-H. H.; Ouassou, A.; Sbay, H.; Kremer, A.; Petit, R. J. (Molecular Ecology, 2001)
Chloroplast (cp) and mitochondrial (mt) DNA variation were studied in 97 populations of cork oak (Quercus suber) in Morocco; in 31 of these populations, holm oak (Quercus ilex), a clearly distinct species, also occurred and was compared with Q. suber. Three cpDNA and one mtDNA primer pairs were used in the survey, each in combination with one restriction enzyme. Six haplotypes belonging to two very divergent lineages were detected; one lineage predominates in each species, and is probably ancestral, as inferred from comparisons with other oak species. In the mixed-species populations, cytoplasmic genomes were frequently shared across species, as indicated by an introgression ratio of 0.63. This index is a new measure of the propensity of species to share locally genetic markers, varying from zero (complete differentiation) to one (no differentiation). By contrast, more closely related deciduous oak species (Q. robur, Q. petraea and Q. pubescens) have introgression ratios varying from 0.82 to 0.97. The introgression events appear to have been more frequent in the direction Q. ilex (female) × Q. suber (male), a finding which seems attributable to the flowering phenology of these two species. This asymmetry may have favoured immigration of Q. suber beyond its main range, in regions already colonized by Q. ilex. There, rare hybridization and further introgression through long distance pollen flow have established populations that are morphologically indistinguishable from Q. suber but that have cytoplasmic genomes originating from the local Q. ilex populations.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd accession-num: 11555243
Keywords: Chloroplast; Chloroplast: genetics; cpDNA; DNA; Evolution; Genetic; Genetic Markers; Genetic Variation; Genetic: genetics; geographical structure; Haplotypes; Hybridization; introgression; Mitochondrial; Mitochondrial: genetics; Models; Molecular; Morocco; mtDNA; PCR–RFLP; Quercus; Quercus: genetics; Trees; Trees: genetics